The Humanities and Higher Education - Duguid, Stephen (Canadian Journal of Higher Education, 1984)
After a long period of decline the humanities seem to be undergoing a kind of renaissance, with specialized institutes, a renewed rhetoric and talk of an academic core curriculum being the chief indications. The causes of the decline are seen as springing from a sustained intellectual attack by the sciences and social sciences, the disillusioning impact of fascism developing in the heart of Western humanism, and the dramatic social and economic changes of the past 200 years. Contemporary advocates of the humanities are seen as falling into three groups: the traditionalists who argue for an implicit worth of the humanities; pragmatists who see the humanities as having real use-value in terms of contemporary social issues; and radicals who see the humanities as a force for social change. Examples are offered of each of these approaches and their strengths and weaknesses analyzed.